1974
DOI: 10.1172/jci107898
|View full text |Cite
|
Sign up to set email alerts
|

The “No-Reflow” Phenomenon after Temporary Coronary Occlusion in the Dog

Abstract: A B S T R A C T The role of microvascular damage in the genesis of the "no-reflow" phenomenon was investigated in the left ventricular myocardium of dogs subjected to temporary occlusions of a major coronary artery for 40 and 90 min. Intravenous carbon black or thioflavin S (a fluorescent vital stain for endothelium) were used to demonstrate the distribution of coronary arterial flow in control and damaged myocardium. These tracers were injected simultaneously with release of the coronary occlusion or after 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
794
3
27

Year Published

1988
1988
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,720 publications
(858 citation statements)
references
References 13 publications
17
794
3
27
Order By: Relevance
“…Based on morphological2 and functional studies,43 microvascular obstruction may have structural and functional components,44 reflecting irreversible (ie, endothelial disruption) and reversible (eg, microvascular spasm, extrinsic edema) components. Myocardial hemorrhage reflects the aggregation and extravasation of erythrocytes4, 20, 45 and is a manifestation of severe microvascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Based on morphological2 and functional studies,43 microvascular obstruction may have structural and functional components,44 reflecting irreversible (ie, endothelial disruption) and reversible (eg, microvascular spasm, extrinsic edema) components. Myocardial hemorrhage reflects the aggregation and extravasation of erythrocytes4, 20, 45 and is a manifestation of severe microvascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired tissue reperfusion after successful recanalization of an epicardial coronary artery has been documented both in animals 6 and in patients [7][8][9][10][11] with AMI. Thus, the degree of functional recovery is related to the extent of microvascular damage.…”
Section: St-segment Resolution and Myocardial Perfusionmentioning
confidence: 99%
“…This socalled "low or no-reflow" phenomenon was first described by Kloner et al in an animal model. 6 Thereafter, this phenomenon has been evaluated by various methods, including myocardial contrast echocardiography (MCE), 7,8 scintigraphy, 9,10 and positron emission tomography (PET) 11 in patients with AMI. However, these techniques are costly and unavailable in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies demonstrated impaired microvascular perfusion which led to the proposal that luminal obstruction by thromboembolic debris and endothelial cell edema is the main cause of the pathology observed (Kloner et al, 1974). However, it is now established that inflammatory cytokines play a crucial role in initiating microvascular damage (Nian et al, 2004).…”
Section: Discussionmentioning
confidence: 99%